Age- and Gender-Based Differences in Nest-Building Behavior and Learning and Memory Performance Measured Using a Radial Six-Armed Water Maze in C57BL/6 Mice - Xiang-Dong Xiong; Wei-Dong Xiong; Shang-Shen Xiong; Gui-Hai Chen (Behavioural Neurology)
Background. Understanding age-based and gender-based behavioral changes is becoming more important as a greater percentage of people lives longer worldwide. In this study, a C57BL/6 mouse animal model was used to study age-based and gender-based behavioral differences using nest building and radial six-armed water maze (RAWM) testing. Methods. In C57BL/6 mice, nest-building behavior was recorded as nesting scores, while spatial learning and memory behaviors were assessed using RAWM platform search errors and latencies. Results. In the nest-building test, nest building significantly declined in nineteen 25-month-old mice compared to that of twenty-three 7-month-old mice. Meanwhile, nest building in 25-month-old mice was lower for eight male mice than for eleven female mice, while no significant gender differences were observed in nest building of 7-month-old mice. RAWM performance also declined in aged versus nonaged adult mice, while no significant gender differences were observed in average RAWM performance regardless of age. Conclusions. In adult C57BL/6 mice, nest building is a sensitive indicator for detecting both age- and gender-based behavioral declines, while RAWM performance, an assessment of spatial learning and memory behaviors, is not sensitive to gender but significantly declines with aging. Therefore, for a C57BL/6 mouse model of aging, both nest building and RAWM should be useful to further study mechanisms involved in behavioral decline with aging.